China and Latin America: perceptions, challenges, and opportunities - Paulo G. Fagundes Visentini; Bruna Santos (MONDE CHINOIS NOUVELLE ASIE, 2014)
In 1980 the collective economic output of Latin America was seven times larger than China’s. Now China’s economy is larger than all of the economies in Latin America combined. According to the International Monetary Fund, China will overtake the United States and become the world’s largest economy in 2016. Not only the recent economic performance and macroeconomic indicators of China, but also of the three other members of the acronym BRICs contribute to a more careful consideration of their possibilities. All of them represent large domestic market and more likely to obtain ‘growth-led exports’ rather than ‘export-led growth’. This condition implies a proactive role in international relations. Latin America is a promising strategic trade partner for China for diversifying export destinations, and also for safeguarding commodity import security. Besides that, with respect to trade and investment, the availability of China as an alternative market was one factor leading Latin America away from the Free Trade Area of the Americas trading regime oriented according to United States’ interest.